(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2024)
As the term indicates the Big data it means we are work for the something big or can say something large in the Amount, Data the high volume is known as the big data.Now a Day for storing the data file in the Computer Science Engineering we are used the Hard disk, some of the storage place , these storage device may store the data in a Giga byte capability and Terabyte capability or many more, Now a day we are used the some new technology call the cloud environment. So in this work I am study the big data storing process in the Cloud environment, big data fetching from the cloud in a securer manner. So in this dissertation work I am also include the some information about the existing work and some of the algorithm that war already proposed by the researcher in the various paper. My work is based on the Attribute-Based Encryption(ABE) is promising technique to ensure the end-to-end security of big data in the cloud However, the policy updating has always been a challenging issue when ABE is used to construct access control schemes.